Data from: Connectivity and population structure in a marginal sea - a review - Henriksson, Simon; Jorde, Per Erik; Berkström, Charlotte; Søvik, Guldborg; De Wit, Pierre; Knutsen, Halvor; Moland, Even; André, Carl; Jahnke, Marlene (University of Gothenburg, 2025)
Supplementary tables for the Review article "Connectivity and Population Structure in a Marginal Sea - a Review" (https://doi.org/10.1111/ddi.70056). Contains information on connectivity and population structure within marine species inhabiting the Skagerrak sea, summarised from scientific studies published between the years 1990 and 2023.

Table S1: List of all 484 scientific studies that were screened, as well as information regarding whether they were included in the literature review.

Table S2: Contains extracted data from the 172 scientific studies, published between 1990 and 2023, that were reviewed with regard to connectivity and population structure in the Skagerrak. The data includes information about both the studies' methodology (such as scientific discipline, spatial and temporal scale, and sample size) and results (such as which populations were identified and estimated connectivity between different regions).

Table S3: Detailed summary of the scientific studies that studied contemporary connectivity on a "large" scale (between the Skagerrak sea and adjacent seas). For species with information from several studies, a concensus result for the species was created.

Table S4: Detailed summary of the scientific studies that studied contemporary connectivity on a "small" scale (within the Skagerrak sea). For species with information from several studies, a concensus result for the species was created.

Table S5: Detailed summary of the scientific studies that studied population structure, both within the Skagerrak Sea and between the Skagerrak and adjacent seas. For species with information from several studies, a concensus result for the species was created.

Tables S6-S7: Settings for the BARRIER analysis conducted in the study.

For more detailed descriptions of the content we refer to the text in the original study.

This dataset is listed as "Deliverable 2.2" of the MARHAB project (Horizon Europe, grant number 101135307).

Tilläggstabeller ("supplementary tables") till review-artikeln "Connectivity and Population Structure in a Marginal Sea - a Review" (https://doi.org/10.1111/ddi.70056). Innehåller information om konnektivitet och populationsstruktur inom marina arter som lever i Skagerrak, sammanställt från vetenskapliga studier publicerade mellan år 1990 och 2023.

Tabell S1: Lista över alla 484 vetenskapliga studier som granskades, samt information om huruvida de inkluderades i litteraturstudien.

Tabell S2: Innehåller sammanställningar av extraherad data från de 172 vetenskapliga studier, publicerade mellan 1990 och 2023, som granskades med avseende på konnektivitet och populationsstruktur i Skagerrak. Data inkluderar information om både studiernas metodik (såsom vetenskaplig disciplin, spatial och temporal skala och stickprovsstorlek) och deras resultat (såsom vilka populationer som identifierats och estimerad konnektivitet mellan olika områden).

Tabell S3: Detaljerad sammanställning av de vetenskapliga studier som studerade kontemporär konnektivitet på "stor" skala (mellan Skagerrak och omgivande hav). För de arter där information fanns från flera olika studier så sammanställdes ett koncensus-resultat för arten.

Tabell S4: Detaljerad sammanställning av de vetenskapliga studier som studerade kontemporär konnektivitet på "liten" skala (inom Skagerrak). För de arter där information fanns från flera olika studier så sammanställdes ett koncensus-resultat för arten.

Tabell S5: Detaljerad sammanställning av de vetenskapliga studier som studerade populationsstruktur, både inom Skagerrak och mellan Skagerrak och omgivande hav. För de arter där information fanns från flera olika studier så sammanställdes ett koncensus-resultat för arten.

Tabell S6-S7: Inställningar för den BARRIER-analys som utfördes i studien.

För utförligare beskrivning av innehållet hänvisar vi till originalstudiens text.

Detta dataset är listat som "Deliverable 2.2" för MARHAB-projektet (Horizon Europe, anslag nummer 101135307).
Data från: Connectivity and population structure in a marginal sea - a review
Keywords: fisheries management; förvaltning av fiskerier; telemetry; telemetri; oceanography; oceanografi; population genetics; populationsgenetik; animal migration; migration (biologi); Phycodrys rubens; ekblading; Fucus serratus; sågtång; Fucus vesiculosus; blåstång; Laminaria hyperborea; stor-tare; Ceramium tenuicorne; ullsläke; Saccharina latissima; skräppe-tare; Amphibalanus improvisus; slät havstulpan; Prymnesium polylepis; Skeletonema marinoi; Pandalus borealis; nordhavsräka; ctenolabrus rupestris (linnaeus, 1758); desmophyllum pertusum (linnaeus, 1758); gasterosteus aculeatus linnaeus, 1758; gyrodactylus gondae huyse, malmberg & volckaert, 2004; hesionides arenaria friedrich, 1937; labrus bergylta ascanius, 1767; magallana gigas (thunberg, 1793); nonionella stella cushman & moyer, 1930; phoca vitulina linnaeus, 1758; pomatoschistus minutus (pallas, 1770); scophthalmus maximus (linnaeus, 1758); strongylocentrotus droebachiensis (o.f. müller, 1776); symphodus melops (linnaeus, 1758); thunnus thynnus (linnaeus, 1758); coryphaenoides rupestris gunnerus, 1765; gadus morhua linnaeus, 1758; mytilus edulis linnaeus, 1758; phocoena phocoena (linnaeus, 1758); syngnathus typhle linnaeus, 1758; nephrops norvegicus (linnaeus, 1758); cyclopterus lumpus linnaeus, 1758; littorina saxatilis (olivi, 1792); platichthys flesus (linnaeus, 1758); pleuronectes platessa linnaeus, 1758; sprattus sprattus (linnaeus, 1758); zostera marina l.; idotea balthica (pallas, 1772); mnemiopsis leidyi a. agassiz, 1865; salmo trutta linnaeus, 1758; homarus gammarus (linnaeus, 1758); ammodytes marinus raitt, 1934; anguilla anguilla (linnaeus, 1758); carcinus maenas (linnaeus, 1758); solea solea (linnaeus, 1758); cancer pagurus linnaeus, 1758; botryllus schlosseri (pallas, 1766); ciona intestinalis (linnaeus, 1767); clupea harengus linnaeus, 1758; connectivity; konnektivitet; larval dispersal; larvspridning; conservation biology; bevarandebiologi; population structure; populationsstruktur; biophysical modelling; biofysisk modellering; Natural Sciences; Naturvetenskap; Environmental Sciences; Miljövetenskap; Physical Geography; Naturgeografi; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Genetics and Genomics; Genetik och genomik; Ecology; Ekologi; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Fish and Aquacultural Science; Fisk- och akvakulturforskning; Environmental Sciences and Nature Conservation; Miljö- och naturvårdsvetenskap; Environmental Economics and Management; Miljöekonomi och förvaltning